Bulbophyllum yarlungzangboense (Orchidaceae; Epidendroideae; Malaxideae), a new species from Tibet, China - Li, Jian-Wu; Wang, Xi-Long; Wang, Cheng-Wang; Pan, Bo; Song, Zhu-Qiu; Jin, Xiao-Hua (Phytotaxa, 2019)
Bulbophyllum yarlungzangboense, a new species of Orchidaceae from Tibet, China is described and illustrated, it is morphologically similar to B. gamblei and B. shweliense, but can be easy distinguished from the later by petals ovate-oblong, stelidis triangular, base of column foot with V-shape cushion. The new species is tentatively assigned to sect. Desmosanthes based on morphological characters.